2008
DOI: 10.1051/vetres:2007056
|View full text |Cite
|
Sign up to set email alerts
|

Atypical/Nor98 scrapie: properties of the agent, genetics, and epidemiology

Abstract: -Atypical/Nor98 scrapie cases in sheep were diagnosed for the first time in Norway in 1998. They are now identified in small ruminants in most European countries and represent an increasingly large proportion of the scrapie cases diagnosed in Europe. Atypical/Nor98 scrapie isolates have shown to be experimentally transmissible into transgenic mice and sheep but the properties of the TSE agent involved, like its biological and biochemical features, are so clearly distinct from the agent involved in classical sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
269
1
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(297 citation statements)
references
References 40 publications
17
269
1
4
Order By: Relevance
“…PrP genotypes of the donor animals (sheep and goat) did not notably influence the incubation time either. Further analyses demonstrated that all the atypical cases transmitted so far involve a unique strain, closely related if not identical to that present in Nor98 cases that were discovered earlier on in Norway ( [17,18,119] and our unpublished data). Notably, this strain exhibits fairly high infectious titre, including in ARR-homozygous sheep [119].…”
Section: Assessment Of Scrapie Strain Diversity With Transgenic Mousesupporting
confidence: 57%
See 1 more Smart Citation
“…PrP genotypes of the donor animals (sheep and goat) did not notably influence the incubation time either. Further analyses demonstrated that all the atypical cases transmitted so far involve a unique strain, closely related if not identical to that present in Nor98 cases that were discovered earlier on in Norway ( [17,18,119] and our unpublished data). Notably, this strain exhibits fairly high infectious titre, including in ARR-homozygous sheep [119].…”
Section: Assessment Of Scrapie Strain Diversity With Transgenic Mousesupporting
confidence: 57%
“…The abnormal PrP associated with these atypical cases is characterized by a lower resistance to protease digestion as compared to classical scrapie. Furthermore, confirmatory neuropathological methods were often inconclusive [18]. Atypical scrapie has been diagnosed in sheep carrying various PrP genotypes, including those homozygous for ARR [40,137,141].…”
Section: Tse In Sheep and Goatsmentioning
confidence: 99%
“…The atypical scrapie form Nor98 (Benestad et al 2008), associated with the variation L141F, has not been described in Brazil. In our work we have found all animals to be of the L/L homozygous genotype.…”
Section: Resultsmentioning
confidence: 96%
“…The details of PrP genetics in atypical scrapie are presented in the special issue ("Prion diseases in animals") by Benestad et al [10]. However, it is important to highlight here some of the genetic differences between classical and atypical scrapie which are the topic of current TSE research.…”
Section: Atypical Scrapie In Sheepmentioning
confidence: 99%